Peran APIP dan Efektivitas Pengendalian Korupsi dalam Mendorong Capaian SDG 6 di Indonesia - Fitria E. Malelea; Sakalindu Sakalindu Kirana Magyanda Uttunggadewi; Seto Ferdy Zuzanto (Universitas Katolik Soegijapranata Semarang, 2026)
This study investigates whether internal audit capability and the effectiveness of corruption control contribute to the achievement of Sustainable Development Goal (SDG) 6 across 541 local governments in Indonesia. Employing a quantitative design and multiple regression analysis on cross-sectional data from 2021, the research explores how institutional governance factors shape regional performance in the provision of clean water and sanitation services. The empirical findings reveal that stronger corruption control is associated with significantly higher SDG 6 performance, whereas internal government audit capability does not exhibit a statistically meaningful effect. These results suggest that outcomes in basic service delivery are driven more by governance quality, budget integrity, and local social capacity than by formal organizational attributes of internal oversight alone. Consequently, strengthening anti-corruption mechanisms and promoting more accountable and transparent public management are essential to accelerating progress toward SDG 6. The study provides evidence that policy efforts should prioritize governance effectiveness and responsiveness to community needs in order to achieve sustainable improvements in water and sanitation services at the local level.